Meningitis of hantavirus etiology - A. A. Garbuzov; Yu. A. Fedkina; A. L. Bairakova; O. L. Timchenko; D. A. Khavkina; T. A. Ruzhentsova; P. V. Chukhliaev (Журнал инфектологии, 2023)
The article describes a clinical case of serous meningitis in a patient with confirmed hemorrhagic fever with renal syndrome (HFRS). Despite the moderate-severe course of the disease with moderate hemorrhagic syndrome, the patient had the development of acute renal failure with the simultaneous occurrence of a rare complication – inflammation of the meningeal membranes caused by hantavirus.